2010
DOI: 10.1177/0300985810375245
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Feline Calicivirus Receptor Junctional Adhesion Molecule A in Feline Tissues

Abstract: Junctional adhesion molecule A (JAM-A) is an immunoglobulin superfamily protein that plays an important role in the assembly and maintenance of tight junctions and the establishment of epithelial cell polarity. The feline JAM-A (fJAM-A) is a functional receptor for feline calicivirus (FCV). Among natural diseases associated with FCV infection, isolates that cause oral vesicular disease are detected in epithelial cells; however, isolates that cause systemic disease are detected in multiple cell types. The distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…Most of the receptor studies are done in cells cultured in monolayers [ 33 , 34 , 35 ]. Monolayer cultures, however, are not representative for tumors when it comes to cell–cell interactions, since the cells are forced to grow on a plastic substrate leaving the apical side exposed to the culture medium and only small areas contact the neighboring cells.…”
Section: Reovirus’ Engagement To Cell Surface Moleculesmentioning
confidence: 99%
“…Most of the receptor studies are done in cells cultured in monolayers [ 33 , 34 , 35 ]. Monolayer cultures, however, are not representative for tumors when it comes to cell–cell interactions, since the cells are forced to grow on a plastic substrate leaving the apical side exposed to the culture medium and only small areas contact the neighboring cells.…”
Section: Reovirus’ Engagement To Cell Surface Moleculesmentioning
confidence: 99%
“…There was significant relief of the symptoms of oral ulcers, especially in cats who received NTZ at 3 dpi, (Supplementary Material S2). The amount of FCV in the trachea and lungs, which are easily infected by FCV (Pesavento et al, 2011), was significantly reduced after treatment with different doses of NTZ, and this result was confirmed by immunohistochemistry. By analyzing complete blood counts and biochemical results, we found that systemic symptoms were alleviated in cats that received NTZ.…”
Section: Discussionmentioning
confidence: 56%
“…When given a certain dose of pF(ab') 2 , the viral loads in the cats' tracheas, lungs and spleens were significantly decreased in both the preventive and therapeutic groups (p < 0.05). These organs produce the feline junctional adhesion molecule A (fJAM-A), a FCV-specific receptor [21]. The reduction in viral load and virus shedding demonstrated that pF(ab') 2 inhibited the proliferation of FCV in cats.…”
Section: Discussionmentioning
confidence: 99%